Using X-ray continuum-fitting to estimate the spin of MAXI J1305–704. Issue 4 (9th February 2023) - Feng, Ye; Steiner, James F; Ramirez, Santiago Ubach; Gou, Lijun
ABSTRACT: MAXI J1305–704 is a transient X-ray binary with a black hole primary. It was discovered on 2012 April 9, during its only known outburst. MAXI J1305–704 is also a high inclination low-mass X-ray binary with prominent dip features in its light curves, so we check the full catalogue of 92 Swift /XRT continuous observations of MAXI J1305–704, focusing only on the stable spectra. We select 13 'gold' spectra for which the rms <0.075 and the coronal scattered fraction $f_{sc} \lesssim 25$ per cent. These 'gold' data are optimal thermal-state observations for continuum-fitting modelling, in which the disc extends to the innermost stable circular orbit and is geometrically thin. The black hole spin was unknown for this object before. By utilizing the X-ray continuum fitting method with the relativistic thin disc model kerrbb2 and supplying the known dynamical binary system parameters, we find MAXI J1305–704 has a moderate spin ($a_{*}=0.87_{-0.13}^{+0.07}$ ) at a 68.3 per cent confidence level. This is the first determination of MAXI J1305–704's spin.